Proceedings of the 6th ACM International Conference on Image and Video Retrieval 2007
DOI: 10.1145/1282280.1282347
|View full text |Cite
|
Sign up to set email alerts
|

A nearest-neighbor approach to relevance feedback in content based image retrieval

Abstract: High retrieval precision in content-based image retrieval can be attained by adopting relevance feedback mechanisms. The main difficulties in exploiting relevance information are i) the gap between user perception of similarity and the similarity computed in the feature space used for the representation of image content, and ii) the availability of few training data (users typically label a few dozen of images). At present, SVM are extensively used to learn from relevance feedback due to their capability of ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 35 publications
0
51
0
Order By: Relevance
“…In this work we resort to a technique proposed in [7] where a score is assigned to each image of a database according to its distance from the nearest image belonging to the target class, and the distance from the nearest image belonging to a different class. This score is further combined to a score related to the distance of the image from the region of relevant images.…”
Section: K-nn Relevance Feedbackmentioning
confidence: 99%
“…In this work we resort to a technique proposed in [7] where a score is assigned to each image of a database according to its distance from the nearest image belonging to the target class, and the distance from the nearest image belonging to a different class. This score is further combined to a score related to the distance of the image from the region of relevant images.…”
Section: K-nn Relevance Feedbackmentioning
confidence: 99%
“…Each image is ranked according to a relevance score depending on nearest neighbor distances. This approach allows recalling a higher percentage of images with respect to SVM-based techniques [22] there after quotient space granularity computing theory into image retrieval field, clarify the granularity thinking in image retrieval, and a novel image retrieval method is imported. Firstly, aiming at the Different behaviors under different granularities, obtain color features under different granularities, achieve different quotient spaces; secondly, do the attribute combination to the obtained quotient spaces according to the quotient space granularity combination principle; and then realize image retrieval using the combined attribute function.…”
Section: Recent Workmentioning
confidence: 99%
“…Every image is ranked according to a relavamce score depending on the nearest neighbor distance. The author has reported that this method outperforms the support vector machine [3]. Wei Bian et al proposed a biased discriminant Euclidean embedding which models the intraclass geometry and interclass discrimination and hence solves the undersampled problem [4].…”
Section: Introductionmentioning
confidence: 99%